Rational analysis of authentication protocols based on NGUYEN L H scheme - Xing-hua LI; Ling-juan DENG; Yuan ZHANG; Jian-feng MA (Tongxin xuebao)
Using the ideas of game theory,NGUYEN L H transformed two families of authentication protocols where the honest party transmitted some useless data with probability α before the normal protocol run,so that even if an attacker attacks a protocol,the attacker’s payoff will still be lower than that when it does not.In such a way,the security of the protocol was guaranteed.However,this scheme suffers from two shortcomings:the considered is too attacker powerful,and only its payoff was considered and the cost of the attacks was ignored; the situation in which the honest node would choose to send useless data was not considered.To improve this scheme,the value of α,with the consideration of the attack cost,of which the value is more general was given.What’s more,the attack probability β was introduced.Based on this,the precondition that the honest node transmits the useless data was presented,as well as the value of α under the different β values.Compared with the original scheme,this results are more generic and comprehensive.Meanwhile,through a case analysis in the P2P network,the correctness of the conclusion is proved.